Characteristics Of Payments For Lawyer Services, The Concept Of Working Funds And Effective Ways Of Accounting For Them - Turaev Shakhriyor Shodiyorovich. (Academia One, 2025)
This article describes the activities of lawyers providing legal services in developed countries in order to ensure their protection, their fee-the amount of remuneration, the procedure for its provision, etc. According to the expert, the provision of legal services should help reduce risks for the self-employed, including those who use the services of lawyers with optimal accounting conditions. At the same time, a mechanism has appeared in the accounting department of the law firm that allows collecting funds spent on its maintenance from the debtor
Keywords: legal services; funds of the self-employed; optimal working conditions